2012
DOI: 10.1007/s12161-012-9497-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sample Preparation Procedures for Trace Element Determination in Brazilian Propolis by Inductively Coupled Plasma Optical Emission Spectrometry and Their Discrimination According to Geographic Region

Abstract: Propolis is a complex mixture of substances collected by honeybees from buds or exudates of plants, beeswax, and other constituents, as pollen and sugars. The main purpose of this study was to evaluate two digestion procedures for determination of major, minor, and trace elements (Ba, Ca, Cd, Cr, Co, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, and Zn) in natura propolis samples by inductively coupled plasma optical emission spectrometry (ICP OES). The first procedure studied was an open-vessel digestion using HNO 3 + H 2 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
1
5
1
2
Order By: Relevance
“…Silva et al (2006) have shown that periods of resin scarcity (that overlap with periods of low precipitation) contribute to the increased wax content in propolis. Korn et al (2013) reported that propolis from the Bahia state is a good source of Ca, K, Mg, and Fe; however, comparison of the mean values obtained in the present study showed that the contents of these elements and of Na and Cu were higher, whereas that of Zn was within the reported range. Comparison of the mean values obtained in this study to those previously recorded in the Paraná state (Finger et al, 2014) showed that Ca and Mg concentrations were within the reported range, Zn concentration was higher, and K and Na concentrations were lower.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Silva et al (2006) have shown that periods of resin scarcity (that overlap with periods of low precipitation) contribute to the increased wax content in propolis. Korn et al (2013) reported that propolis from the Bahia state is a good source of Ca, K, Mg, and Fe; however, comparison of the mean values obtained in the present study showed that the contents of these elements and of Na and Cu were higher, whereas that of Zn was within the reported range. Comparison of the mean values obtained in this study to those previously recorded in the Paraná state (Finger et al, 2014) showed that Ca and Mg concentrations were within the reported range, Zn concentration was higher, and K and Na concentrations were lower.…”
Section: Discussioncontrasting
confidence: 83%
“…Korn et al (2013) evaluated macro-and micro-minerals in natural propolis harvested in Bahia state in the northeast of Brazil, and they found that these propolis samples were not contaminated by potentially toxic species and were a good source of magnesium (Mg), calcium (Ca), potassium (K), and iron (Fe). Finger et al (2014) studied the concentrations of 11 representative metals in some regions of the Paraná state in South Brazil, and they demonstrated that the concentrations of aluminum (Al), Ca, and Mg differed in some regions, which could be used to identify not only the geographical origin of propolis, and to identification of specific zones with environmental contamination.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of Mg ( Figure 1A) was due to the presence of this element in the constitution of propolis applied (Table 1), which was observed in the formation of propolis in other studies (Marcucci, 2008;Pataca, 2006; Gong et al, 2012;Korn et al, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…e values found were similar to our results, which ranged from 2.63 to 11.35 mg•g − 1 . However, the values found by Korn et al [47] in samples of propolis from several regions of Bahia were smaller, with values between 0,199 and 1,892 mg•g − 1 . Figure 1(a) shows the correlation between PC 1 and PC 2, the main components of the propolis studied in this work.…”
Section: Resultsmentioning
confidence: 71%